Gender, equitiy and peace in Guatemala, 1996-2015 (2021)
Objective: the study exposes the state initiatives in favor of women, derived from the Peace Agreements in Guatemala; it also analytically highlights some of the weaknesses identified and the structural aspects that adversely influence their implementation and results. Originality/support: it is mainly the comparative review of public policies, which provides references for future initiatives or to improve the existing ones. Method: the research is qualitative in nature, descriptive and analytical. Strategy/ information gathering:Interpretation strategies based on the hermeneutic and holistic approaches were used, due to the need to identify the path of women and their achievements, but also considering the multidimensionality of the problem. Conclusions: from the study that there are still legal norms that legitimize discriminatory practices against women and that gender institutions need to be strengthened in order to comply with their mission mandate. Public policies have evolved favorably in terms of their design and strategic management, but their effective implementation and impact is not yet evident. Gender asymmetries require changes both in institutional practices and in social relations in which inequality is a normality.